2010
DOI: 10.1007/s00484-010-0357-6
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal clothing ensembles based on weather forecasts, with particular reference to outdoor winter military activities

Abstract: Military and civil defense personnel are often involved in complex activities in a variety of outdoor environments. The choice of appropriate clothing ensembles represents an important strategy to establish the success of a military mission. The main aim of this study was to compare the known clothing insulation of the garment ensembles worn by soldiers during two winter outdoor field trials (hike and guard duty) with the estimated optimal clothing thermal insulations recommended to maintain thermoneutrality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Ainslie et al [ 42 ] observed T re values between 37.5 and 38 °C during 7.5 h of hill walking (9.5 kg external load carriage) when consuming 3000 kcal (about a 1700 kcal deficit). Similarly, Morabito et al [ 23 ] reported pill temperatures of ~38 °C after a 12-km winter movement in 3 h, about a 1 °C increase from rest. Sleeping deep body temperatures in the current study were similar to that observed during a 54-h physically intense, energy intake-restricted field training exercise in warmer ambient conditions [ 15 ], indicating that the insulation from clothing, sleeping bags, and shelter was adequate to protect against freezing injury during the two winter training exercises.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Ainslie et al [ 42 ] observed T re values between 37.5 and 38 °C during 7.5 h of hill walking (9.5 kg external load carriage) when consuming 3000 kcal (about a 1700 kcal deficit). Similarly, Morabito et al [ 23 ] reported pill temperatures of ~38 °C after a 12-km winter movement in 3 h, about a 1 °C increase from rest. Sleeping deep body temperatures in the current study were similar to that observed during a 54-h physically intense, energy intake-restricted field training exercise in warmer ambient conditions [ 15 ], indicating that the insulation from clothing, sleeping bags, and shelter was adequate to protect against freezing injury during the two winter training exercises.…”
Section: Discussionmentioning
confidence: 77%
“…The degree of physiological strain is similar to hikes/military movements conducted over a 3–7.5 h timeline while carrying external masses of 9.5–31 kg [ 23 , 42 , 43 ]. In these “like” studies, HRs ranged from 110 to 135 beats min −1 (55–73% HR max ), similar to that observed in the present study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Tako je optimalni oblačilni sistem, ki ga nosi uporabnik, tisti, ki zagotovi vzdrževanje temperature jedra človeškega telesa med 36 in 38 °C in temperature na površini kože med 20 in 35 °C [1]. Nadgradnja optimalnega oblačilnega sistema je zmogljiva programska oprema, s pomočjo katere se za različna delovna okolja lahko napove optimalna toplotna izolacija [2]. Takšen sistem in oprema sta za končnega uporabnika z vidika pregretja ali podhladitve izjemno pomembna.…”
Section: Uvodunclassified
“…The current focus in the development of manikins is the incorporation of numerical thermoregulatory models in the control systems regulating heat loss patterns in manikins (Wissler, 1985;Fiala 2001). Recent studies , Zavec Pavlinic et al 2011, Morabito et al 2011) have demonstrated that data regarding thermal and evaporative resistance obtained with sweating thermal manikins are useful for simulating human thermoregulatory responses to different environmental conditions, at different levels of work activity.…”
Section: Risk Of Injurymentioning
confidence: 99%